(untitled) (Szociológiai Szemle, 2024)
Recent works on the philosophy of the social sciences and on the philosophy of the mind have raised questions about the role and epistemological status of rationality in the attribution of beliefs and desires. After characterizing rational action as expected utility maximization, the paper attempts to show (1) that rationality plays a role in social sciences comparable to a method of measurement and (2) that this implies the of acceptance of a weak form of externalism in the philosophy of the mind.